PRESERVASI PENGETAHUAN DALAM TRADISI LISAN SENI PERTUNJUKAN RANDAI DI MINANGKABAU SUMATERA BARAT - Primadesi, Yona (Jurnal Kajian Informasi dan Perpustakaan, 2013)
This paper aims to identify the elements in the oral art tradition of Minangkabau randai art, the preservation activities of knowledge that have been done, the constraints in the process of preservation of knowledge, as well as the steps that can be done in order to preserve the knowledge contained in the oral tradition of Minangkabau randai art performance. The method used is research method with qualitative approach and data collection through interview and document analysis method. The result of this research concludes that randai is an artistic tradition of society that is built from three important components, namely silek, kaba, and dendang or gurindam. Each element supports each other to build the main function of randai as representation and communication media of adat as well as cultural identity of Minangkabau society. The development, bakaba tradition of babangkito Minangkabau society accelerate the process of socialization and transfer of randai along with knowledge in it. But it also becomes an obstacle and hamper the preservation of originality of randai art itself. Preservation activities that have been done in general in the form of socialization activities in the form of direct face-to-face interaction and imitation process. Externalization in the form of documenting the tradition has begun, but not yet on the level of analysis, repackaging, and transfer of knowledge so that most of the knowledge is only stored in government agencies such as the Department of Tourism.Â